A comparative study of phonetogram parameters among female trained Hindustani classical singers, untrained singers and non-singers - Bandhopadhyay, Ankur; Chaterjee, Indranil; Dey, Sanghamitra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Vocal sound is based on the complex yet co-ordinated interaction of phonatory system, resonatory system and respiratory system. Phonetography is a practicable and readily accessible method to investigate and map the quantitative potentialities of vocal output. The objectives of the present study were to determine the phonetogram of trained (Hindustani classical) singers, untrained singer sand non-singers elicited from singing as well as speech task to see if statistically significant differences were present which may indicate an effect of training. Methods: 90 female subjects between the ages 20-45 (mean age 34.2 years for trained subjects, 26.3 years for untrained subjects and 25.8 years for non-singers) divided into three groups each group consisting of 30 subjects. For the singing task, the individuals had to phonate |a| at habitual level by traversing through eight musical scales. In the speech task, the subjects were asked to count from one to twenty in Bengali at habitat level and at Sustainable cohorts of intensity. This was recorded using phonetogram software Dr. Speech (version 4). The parameters considered were fundamental frequency, intensity, semitones and area. Results: The study revealed that in both tasks singing and non-singing task for all three groups in all the four parameters of phonetogram significant differences were seen (p=0.000) at 95% level of confidence. Conclusions: The present study depicted the phonetographic profile of a genre of trained singers and tracked out the parameters on which differences are pronounced between a trained and untrained singer and non-singer.